Cultivating Green Entrepreneurs: A Project-Based Learning Module to Foster Environmental Awareness and Entrepreneurship in Primary Schools - Cahyani, Christina Wahyu; Hartoyo, Agung; Mardiyyaningsih, Asriah Nurdini; Aprinastuti, Christiyanti; Fitriawan, Dona; Nursusanto, Stevanus Widuri; Muskania, Ricka Tesi (FKIP Universitas Lampung, 2025)
Cultivating Green Entrepreneurs: A Project-Based Learning Module to Foster Environmental Awareness and Entrepreneurship in Primary School. Objectives: This research and development aimed to develop a valid, practical, and effective project module product for teaching entrepreneurship and raising environmental awareness, which is crucial for grade V students. This study investigated how a project-based learning module can foster environmental awareness and entrepreneurship character among fifth-grade students. Methods: This study was implemented at Toho State Elementary School, a rural school in West Kalimantan, Indonesia, facing environmental and economic sustainability challenges. This study used the Research and Development (R&D) method by adopting the ADDIE model. The module was to involve students in project activities that combine environmental care with opportunities to earn a living, in line with the local wisdom of the Dayak tribe in Toho. The module was validated by six experts in media, module design, and materials before field testing and implementation with teachers and students at SD Negeri 10 Toho. Participants included students, teachers, and expert validators involved in module testing. Environmental and entrepreneurship character were assessed using observation rubrics and pre–posttest. The practicality aspect of this module was measured through a survey of teachers and students; meanwhile, the effectiveness was assessed using Effect Size. Findings: Data were collected through tests, questionnaires, and interviews. The study found that the project module was feasible based on the expertise assessment. From the fifth graders' classroom teacher's perspective, the module had met 87.5 of % items of practicality and was seen as handy and easy to implement (practical). The findings indicate that the module is a valid and practical tool for integrating sustainability values into primary education. The effectiveness of the implementation of the project module shows that the N-Gain score reaches 55.27% indicating a moderate effect according to Hake’s criteria. Conclusion: The project module is suitable for teaching environmental awareness and entrepreneurship to fifth graders, as it has been validated and practical, though it still needs adjustments to improve its effectiveness. Keywords: project module, environmental care, entrepreneurship, sustainable lifestyle.